(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the incidence of conversion of laparoscopic cholecystectomy to open in patients presenting with gall bladder wall thickness more than 3mm. Also examine the per-operative complications and post-operative wound infection. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Surgery, Central Park Teaching Hospital Lahore from 1stMay 2018 to 30thApril 2019. Materials and Methods: Total 132 patients of both genders with ages 20 to 60 years with gall bladder diseases having wall thickness >3mm were included. Patient’s demographics including age, sex, and duration of disease and thickness of gall bladder wall were recorded after taking written consent. All the patients underwent laparoscopic cholecystectomy. Per-operative complications, conversion to open and post-operative wound infection were recorded. Results: There were 105 (79.55%) females and 27 (20.45%) males with mean age 36.48±13.52 years. Mean duration of disease was 3.95±3.45 years. 92 (69.70%) patients had gall bladder wall thickness 3.5mm to 4.5mm, 29 (21.97%) patients had 4.6 to 5.5mm wall thickness and 11 (8.33%) had more than 5.5mm wall thickness. 45 (34.09%) patients had per-operative adhesion, perforation found in 13 (9.85%) patients and per-operative bleeding during separation was found in 50 (37.88%) patients. 17 (12.88%) patients needed conversion to open cholecystectomy. Post-operative wound infection found in 20 (15.15%) patients. Conclusion: Thick walled gall bladder is directly associated to conversion laparoscopic to open cholecystectomy with high rate of per-operative complications and post-operative wound infection.